Masfareeza’s Frozen Food Enterprise / Mariam Osman ... [et al.] - Osman, Mariam; Ibrahim, Nasratul Badrina; Ahmad, Azren Haslina; Md Saman, Norizan (2002)
Masfareeza’s Frozen Food Enterprise Sdn. Bhd. is a business which provides food product in a form of frozen food. We concentrate on Malaysia traditional delicacies which varies to cuurypuff, samosas, apam, roti canai, cucur badak, onde-onde, cucur kacang and doughnut.